Key personality traits of martial arts and world`s top coaches others sports - perspective of creative impact on future martial arts specialists - Predoiu, A.; Predoiu, R.; Makarowski, R.; Gorner, K.; Bota, A.; Mitrache, G.; Grigore, V. (Archives of Budo, 2020)
Background and Study Aim: The personal development process is invaluable for martial arts coaches (and not only), our research increasing awareness of viewing the martial art coach as a performer within the sports performance field. The cognitive aim of current study is knowledge about specific personality traits of coaches of martial arts and top coaches at Olympic, World and European levels others sports.